Carleton and Cornelia Parker: Lives and Labor Economics. Issue 3 (3rd July 2022) - Rutherford, Malcolm
Abstract: Carleton Parker was involved in investigations of the Industrial Workers of the World relating to the Hop Field Riots in California in 1913, and in an attempt to link economics with psychology in the understanding of labor disputes. In this he was influenced by Thorstein Veblen, William McDougall, and by many other psychologists. The culmination of his work was his paper "Motives in Economic Life" given at the AEA meetings in 1917. Parker's work on "labor psychology" generated great excitement at the time, connected him with many other liberal progressives, and was an influence on early members of the institutionalist group. Unfortunately, Parker died in the 1918 influenza pandemic. His wife, Cornelia Parker, worked to secure his legacy and attempted to carry on his work. She wrote a biography of her late husband, edited his papers, moved to New York to attend The New School and did her own research on the working woman. This paper deals with the lives and work of these two extraordinary people, and the intellectual environment that surrounded them.